DEVELOPMENT OF A PORTABLE MOTOR VEHICLE EMISSION TEST SYSTEM BASED ON ARDUINO WITH ANDROID INTERFACE - Nur Indah; Dimas Aji Pangestu; Satryo Budi Utomo; Rikko Putra Youlia (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2023)
This study takes a comprehensive approach by proposing the design of an innovative emission test tool for motorized vehicles. The primary objective of this tool's design is to establish an alternative emission testing apparatus based on Arduino AT-Mega 2560, proficient in capturing vehicle exhaust emissions. The underlying methodology involves an in-depth investigation of various components, including the MQ2 and MQ7 sensors, microcontrollers, and supplementary sensors. This meticulous observational process aims to unravel the fundamental principles that govern the functionality of these components. Subsequently, the study advances to the prototyping phase, manifesting in the creation of an Android-based emission test system. This system capitalizes on the integration of Arduino programming and App Inventor technology. The integrated system is devised to facilitate sensor data acquisition. The empirical results of the tests indicate that the developed tool effectively measures hydrocarbon gas and carbon monoxide gas concentrations, yielding readings of 6.31% and 3.73%, respectively, under engine conditions ranging from 1500 to 3000 rpm with error in regions 1.4% and 5.1% compared to a commercial instrument. However, during the testing phase, certain challenges surfaced. Notably, the presence of water particles within the tool, coupled with the generation of heat due to the accommodated exhaust gases, increased the temperature within the tool's enclosure. Consequently, the sensors' temperature escalated, resulting in erratic sensor behavior and unstable readings. Nonetheless, a significant advantage of the proposed tool lies in its real-time data visualization capability, which is particularly accessible through Android smartphones. This feature enhances the immediacy of test results, facilitating prompt analysis and decision-making. In conclusion, this study lays the groundwork for an innovative emission testing tool that demonstrates promise in addressing the air quality degradation stemming from vehicular emissions.